Paper, Photography, and a Reflection on Urban Landscape in 1960s Japan. (1st October 2016) - Kim, Gyewon
Abstract : This article investigates how avant-garde photographers have explored the material dimensions of the photographic medium in postwar Japan. In particular, it examines the work of Provoke, a radical artistic group that collectively publicized a specific visualization of the urban landscape during the course of the late 1960s. Rejecting the complacent perspectives of conventional reportage and naïve realism, the Provoke artists attempted to construct a direct synthesis of experimental avant-garde and documentary practice as a useful method of social critique. At the center of Provoke's experimentalism there was an original discourse of document and documentation that brought about a new style of photographs characterized by their rough, blurry, and grainy imagery. Provoke's innovative conceptual approach and method of document creation was mediated through paper as a significant material support of the photographic image. Their experiments with paper brought to the fore the affective dynamics of urban forms, signs, and textuality, through which the artists were able to reflect a new ontology of the city in relation to the specific physical materiality of their documentation.